Kinetika Adsorpsi Pada Penjerapan Ion Timbal Pb2+ Terlarut Dalam Air Menggunakan Partikel Hydroxyapatite - Fernando Susilo; Ahmad Fadli; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This research are to observe the effect of mass adsorbent (hydroxyapatite) and temperature in adsorption of metal ions Pb2+ using adsorbent hydroxyapatite (HAp) and determine a suitable adsorption kinetics model. Pb2+ solution 9,982 mg/L of 500 mL where mixed with variation of mass HAp (0.3 g, 0.5 g and 0.9 g)  in a glass beaker while stirred with rate 100 rpm at variation temperature (27, 40, and 50 oC).Pb2+ solution was taken at a certain time, then the solution  filtered and analyzed by atomic absorption spectrophotometer (AAS). The result showed that the adsorption of metal ions is pseudo second order reaction with the higher mass of adsorbent and with lower temperature. In this research maximum constant value of adsorption kinetic was 0.2758 g/mg.min obtained with mass of adsorbent 0.9 g and temperature of 27 oC. While minimum value of adsorption kinetics constant 0.0389 g/mg.min obtained with mass of adsorbent  0.3 g and temperature of 50 oC.  Keywords:  Adsorption, Hydroxyapatite, Kinetic, Timbale.